Molecular Dynamics Studies Of The Annealing Of Carbon Peapods - Lee, Thong Yan (2018)
In the past 30 years, carbon kept surprising the scientific community given the previous assumption that all carbon structures are already known. Apart from graphite, diamond and amorphous; new carbon allotropes including fullerenes, carbon nanotubes (CNT) and graphenes were discovered in year 1985, 1991 and 2004 respectively. Carbon peapod is a hybrid carbon nanostructure in which fullerenes such as C60 are encapsulated in an outer carbon nanotube. Carbon peapod can be transformed into a double-walled carbon nanotube (DWCNT) through annealing process. In essence, the fullerenes will fuse and form a smaller CNT in the outer CNT which acts as a mold/container. However there are a few research gaps in the simulations of the annealing process, e.g., potential was not applied to the outer CNT of the peapod and long range (van der Waals) interactions was ignored. In this thesis, the structures of three carbon peapods with different diameters are first constructed based on experimentally measured data. The peapods in the study are 13C60@CNT(13, 5), 13C60@CNT(14, 7) and 13C60@CNT(12, 12), where there are 13 C60 molecules in each peapod. Classical molecular dynamics (MD) simulations are performed to study the morphological transition of carbon peapods into DWCNT for the whole annealing process which lasted for 1 ns. All MD simulations are done with LAMMPS and AIREBO is chosen as the potential to simulate the inter- and intra-molecular interactions among the carbon atoms. From the simulated results it is observed that increased reactivity of the carbon peapod is associated with increasing annealing temperature.